Single-Dose Radiation-Induced Oral Mucositis Mouse Model - Maria, Osama Muhammad; Syme, Alasdair; Eliopoulos, Nicoletta; Muanza, Thierry (Frontiers in Oncology, 2016)
The generation of a self-resolved radiation-induced oral mucositis (RIOM) mouse model using the highest possibly tolerable single ionizing radiation (RT) dose was needed in order to study RIOM management solutions. We used 10 week-old male BALB/c mice with average weight of 23 gm for model production. Mice were treated with an orthovoltage X-ray irradiator to induce the RIOM ulceration at the intermolar eminence of the animal tongue. General anesthesia was injected intraperitoneally for proper animal immobilization during the procedure. 10 days after irradiation, a single RT dose of 10, 15, 18, 20, and 25 Gy generated a RIOM ulcer at the intermolar eminence (posterior upper tongue surface) with mean ulcer floor (posterior epithelium) heights of 190, 150, 25, 10, and 10 µm, respectively, compared to 200 µm in non-irradiated animals. The mean RIOM ulcer size % of the total epithelialized upper surface of the animal tongue was RT dose-dependent. At day 10, the ulcer size % was 2%, 5%, 27%, and 31% for 15, 18, 20, and 25 Gy RT, respectively. The mean relative surface area of the total epithelialized upper surface of the tongue was RT dose-dependent, since it was significantly decreased to 97%, 95%, 88%, and 38% with 15, 18, 20, and 25 Gy doses, respectively, at day 10 after RT. Subcutaneous injection of 1 mL of 0.9% saline / 6 hours for 24 hours yielded a 100% survival only with 18 Gy self-resolved RIOM which had 5.6 ± 0.3 days ulcer duration. In conclusion, we have generated a 100% survival self-resolved single dose radiation-induced oral mucositis male mouse model with long enough duration for application in RIOM management research. Oral mucositis ulceration was radiation dose-dependent. Sufficient hydration of animals after radiation exposure significantly improved their survival.